pharmaceutical-sciences 2019
DOI: 10.36468/pharmaceutical-sciences.537
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal Toxicity Associated with Vincristine Treatment

Abstract: Sonawane et al.: Epididymal Toxicity Associated with Vincristine Vincristine, a major player in front line combination chemotherapy of cancer reduces testosterone levels contributing to reproductive toxicity. Much is known about testicular toxicity of vincristine as compared to its effect on epididymis; hence, the present study aimed to evaluate the epididymal toxicity associated with vincristine treatment, which also contributes to the overall reproductive toxicity associated with vincristine. Vincristine was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In addition, the decrease of phosphorus level was significantly decreased in tail region of CS epididymal fluid. Such results are similar to those ion concentrations decreased in both regions of epididymal fluid of rats induced with chemotherapy drug (Sonawane et al., 2019; Turner et al., 1977). It is novel that CS could change the levels of ions in epididymal fluid.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the decrease of phosphorus level was significantly decreased in tail region of CS epididymal fluid. Such results are similar to those ion concentrations decreased in both regions of epididymal fluid of rats induced with chemotherapy drug (Sonawane et al., 2019; Turner et al., 1977). It is novel that CS could change the levels of ions in epididymal fluid.…”
Section: Discussionsupporting
confidence: 86%
“…The regulations of electrolyte concentration and pH in the epididymal fluid are important for processes of sperm maturation and prevention of precocious acrosome reaction. Especially, the sodium ions were found to be the principal cations for sperm motility process (Gadella & Van Gestel, 2004; Sonawane et al., 2019). This study demonstrated the significant decreases of sodium, potassium and chloride levels in the CS epididymal fluid fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Vincristine is a significant vinca alkaloid that is extensively used in front-line combination chemotherapy therapies for cancer. Because of its ability to lower testosterone levels, vincristine contributes to reproductive damage [85]. In addition, Sonawane and colleagues discovered that therapy with vincristine promotes epididymal toxicity, which is another factor that adds to the total reproductive toxicity.…”
Section: Toxicity and Adverse Effectsmentioning
confidence: 99%